The age of trauma: the prevalence and psychological impact of potentially traumatic exposures in South Korea - Son, Gaeun; Jang, Jihee; Hong, Euntaek; Park, Subin; Choi, Yun-Kyeung; Choi, Kee-Hong (Frontiers in Psychiatry, 2025)
BackgroundExposure to potentially traumatic events (PTE) is associated with a range of negative mental health outcomes, including post-traumatic stress disorder (PTSD) and complex PTSD (cPTSD). Although exposure to PTEs is highly prevalent, and their impact on mental health is pervasive, research is mostly limited to diagnosed populations or specific trauma cohorts in the post-pandemic era.MethodsWe conducted an online survey of 1,000 Seoul residents from October 6-12, 2023, using a stratified sampling method. Participants were asked about their traumatic experiences, mental health outcomes, and experiences with mental health services.ResultsMost participants (98.8%) reported that they had experienced at least one PTE. The average number of PTEs reported was 9.19 (SD=7.908). Ninety participants (9%) were categorized as having probable PTSD (2.8% with PTSD only, and 6.2% with cPTSD). The sum of direct and indirect exposures to PTEs of individuals was associated with mental health outcomes, including PTSD symptom severity. Only 34.4% of patients with probable PTSD reported that they had received appropriate mental health services.ConclusionOur results suggest that PTE exposures are highly prevalent, and self-awareness of mental health conditions and utilization of mental health services are low in South Korea. Given the lasting effects of traumatic events and the large number of untreated cases, this study highlights the need for proactive responses to traumatic events and better access to short- and long-term services for traumatized individuals.